Studies on Microbial Fuel Cells with Modified MWNTs Anode Materials - Wang, Juan; Xiong, Hui; Xiong, Zhensheng; Xu, Fangcheng; Fang, Jing; Liu, Fuming; Ling, Yun; Pan, Jianfei; Xie, Yu (Asian Journal of Chemistry, 2015)
The marine exoelectrons S. marisflavi EP1 were intertidal sediments that taken from a marine surface of Xiamen Baicheng Sea. This study examined the electricity production performance of three different anode materials in microbial fuel cells i.e., graphite, multi-walled carbon nanotubes and the esterified multi-walled carbon nanotubes. The results showed that the produced maximum voltage of the above three anode materials were 0.5282 V, 0.4329 V and 0.3123 V, respectively, along with the maximum power densities were 341.6, 241.1 and 151.4 mW/cm2. The maximum power density to use the esterified multi-walled carbon nanotubes as the microbial fuel cell anode was 1.25 times as that of graphite. The growth of bacteria on the surface of the esterified multi-walled carbon nanotubes is faster than that on the surface of the graphite anode. It indicates that esterified multi-walled carbon nanotubes modified anode can significantly increased the electricity production of extracellular electronic metabolic capacity, so as to improve producing electrical properties of the microbial fuel cell.